Bottom-up vs. top-down policies towards the commercialization of university intellectual property - Brent Goldfarb; Magnus Henrekson (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
What national policies are most efficient in promoting the commercialization of university-generated knowledge? We address this question by characterizing and evaluating the policy pursued in Sweden and the US, two countries that put a great deal of resources into university R&D, but follow very different models for commercialization. Despite a leading academic record, there is an impression of laggard rates of commercialization of academic research results in Sweden. Although there exist no micro data to evaluate this impression, we argue that it is likely to be true in part due to the top-down nature of Swedish policies aimed at commercializing these innovations as well as an academic environment that discourages academics from actively participating in the commercialization of their ideas. This sits in stark contrast to a US institutional setting characterized by competition between universities for research funds and research personnel, which in turn has led to significant academic freedoms to interact with industry, including significant involvement in new firms.
Keywords: J24; O31; O32; O57; 330; Academic entrepreneurship; Innovation; Intellectual property; R&D; Spin-off firms; Technology transfer; University-industry relations; Universities and business formation; Hochschulforschung; Forschungskooperation; Wissenstransfer; Vergleich; Schweden; USA